2014
DOI: 10.1093/acprof:oso/9780199860029.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Faith on the Avenue

Abstract: Faith on the Avenue looks at just one street in one city—Germantown Avenue in Philadelphia—and the 80-90 communities of faith that are present on it. Sociologist Katie Day draws from her findings of a seven year study to argue that these religious communities are active agents in their local urban contexts, both shaping and being shaped by it. Far from being a benign presence, these congregations are engaging, and contributing to, the urban ecology in myriad ways and to varying degrees. Their agency, analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The absence of these methods is curious given the visual and material nature of religion and spirituality in the contemporary world. Houses of worship, for example, of all types dot the social landscape (Vergara 2005; Richter 2007; Krieger 2011; Day 2014). The visual permeates religious culture (Morgan and Promey 2001) and images of religion are present throughout popular culture (Nardella 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The absence of these methods is curious given the visual and material nature of religion and spirituality in the contemporary world. Houses of worship, for example, of all types dot the social landscape (Vergara 2005; Richter 2007; Krieger 2011; Day 2014). The visual permeates religious culture (Morgan and Promey 2001) and images of religion are present throughout popular culture (Nardella 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that this is not the first time that some types of conversions articulated in this study have been identified; some have already been the focal point of much of the extant research on converted structures. For example, the storefront church (secular form, mixed function) has been extensively explored and documented by Vergara (2005), Day (2014), Krieger (2011), and many others. So, too, the luxury loft (mixed form, secular function) has captured the attention of Mian (2008), Hackworth and Gullikson (2013), Lynch (2014; 2016), and more.…”
Section: Discussionmentioning
confidence: 99%
“…Scholarly work on sacred-to-secular and secular-to-sacred building conversions has, thus far, focused on case studies of isolated conversions and sets of conversions in a particular city (Day 2014; Krause 2008; Krieger 2011; Lynch 2016; Mian 2008). As a result, we know that this phenomenon is occurring, but nobody knows the prevalence or the locations of these conversions.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation